Comminuted Distal Radial Fracture with Large Rotated Palmar Medial Osteochondral Fragment in the Joint - Gökkus, Kemal (J Orthop Case Rep, 2018)
INTRODUCTION: Intra-articular distal radius fractures have long been massively discussed in the literature, but regarding to fractures that possess rotated volar medial fragment in the joint a few amount papers has been written. In this article, we would like to emphasize the significance of the rotated palmar medial (lunate facet) fragment. CASE REPORT: A 39-year-old man fell from a height of about 3 m and landed on his right outstretched hand; within 40 min, he arrived at our clinic presenting with a severe pain and swelling in his right wrist. Initial X-rays of the wrist revealed dorsal subluxation of the radiocarpal joint with dorsal comminution of the radial articular surface and fracture of the radial styloid process, with (nearly inverted) ~ 140-150° rotation of the palmar medial fragment. With an additional volar approach, the fragment reduced and stabilized with two K-wires and wrist immobilized in external fixator. The patient returned to daily activities without any discomfort and pain after the 1 year from the surgery. CONCLUSION: Overlooking of palmar rotated osteochondral fragment will cause deficiency to build proper pre-operative strategy to approach the reduction of the fragment. The incompetence of reduction will deteriorate the articular surface and lead to early osteoarthritis of the wrist. The surgeon should detect this fragment and should be familiar with volar approaches of the wrist. Above average surgical experience would be needed for successful reduction.